Golimumab as Rescue Therapy for Refractory Immune-Mediated Uveitis: A Three-Center Experience - Miguel Cordero-Coma; Vanesa Calvo-Río; Alfredo Adán; Ricardo Blanco; Carolina Álvarez-Castro; Marina Mesquida; Sara Calleja; Miguel A. González-Gay; José G. Ruíz de Morales (Hindawi Limited, 2014)
Objective. To evaluate, in three Spanish tertiary referral centres, the short-term safety and efficacy of golimumab (GLM) for treatment of immune-mediated uveitis resistant to previous immunosuppressive therapy. Methods. Nonrandomized retrospective interventional case series. Thirteen patients with different types of uveitis that were resistant to treatment with at least 2 previous immunosuppressors were included in this study. All included patients were treated with GLM (50 mg every four weeks) during at least 6 months. Clinical evaluation and treatment-related side effects were assessed at least four times in all included patients. Results. Eight men and 5 women (22 affected eyes) with a median age of 30 years (range 20-38) and active immune-mediated uveitides were studied. GLM was used in combination with conventional immunosuppressors in 7 patients (53.8%). GLM therapy achieved complete control of inflammation in 12/13 patients (92.3%) after six months of treatment. There was a statistically significant improvement in mean BCVA (0.60 versus 0.68, P=0.009) and mean 1 mm central retinal thickness (317 versus 261.2 μ, P=0.05) at the six-month endpoint when compared to basal values. No major systemic adverse effects associated with GLM therapy were observed. Conclusions. GLM is a new and promising therapeutic option for patients with severe and refractory uveitis.